A Study of the Relationship between Oxidative Stress and Risk of Developing Hepatocellular Carcinoma in People with Hepatitis B Infection; A Systematic Review Study - Nour, Hammadi; Maroua, Chouia; Samir, Derouiche (Asian Pacific Journal of Cancer Biology, 2022)
Introduction: Hepatitis B infection is a severe global public health issue. It is the 10th biggest cause of death worldwide. Objective: This review focuses on the relationship between oxidative stress and the risk of developing of acute and chronic hepatitis B complications. Methods: The data were collected by searching Science Direct, Google Scholar, PubMed, Scopus, Springer and National Center for Biotechnology Information (NCBI). The Keywords used as search terms were “Hepatitis B”, “Acute and Chronic hepatitis”, “HBV induced inflammatory reaction”, “hepatitis B and Oxidative stress” and “free radical induced hepatitis B complication”. Results: Chronic infections with chronic active hepatitis, acute or sub-acute hepatic necrosis, cirrhosis, liver failure, and hepatocellular cancer in people with hepatitis B infection are all complications of viral hepatitis. Extrahepatic complications are common in patients with chronic hepatitis infection, including cryoglobulinemia, non-Hodgkin lymphoma, focal lymphocytic sialadenitis, autoimmune thyroiditis, porphyria cutanea tarda, and lichen planus. Wide variations in hepatitis B incubation durations show that the redox state of cells can influence viral activity. Viral replication is more active with more severe oxidative stress, with dispersion from lysed or dead cells. Although the precise mechanisms of ROS participation in the pathogenesis of inflammatory disorders are still debated. Conclusion: Viral activity can be determined by the oxidative stress status of the cells which can be the main cause of the development of hepatocellular carcinoma related to the complications of acute and chronic hepatitis B.